Investigating the Efficiency of Monetary Transmission Channels in Serbia - Jevđović, Gordana (Industrija, 2014)
Abstract: The aim of this paper is to evaluate the effectiveness of monetary policy transmission mechanism in Serbia. By using Johansen cointegration technique, based on VAR/VECM methodology, the impact of selected monetary variables on real economic activity and price level is studied over the period 2007M1-2014M1. Results indicate that the exchange rate pass-through to both output and prices is relatively strong, while the interest rate channel is still underdeveloped and does not appear to play an important role as a monetary transmission mechanism. Such balance of powers is not unexpected having in mind traditionally powerful nexus between exchange rate movements and behavior of all economic agents in Serbia. On the other hand, it should be stressed that a very weak link revealed between key policy interest rate and prices in Serbia does not represent a desirable feature in the adopted inflation targeting regime.